Distribution of the single nucleotide polymorphism C3435T of MDR1 gene among people in Western Australia, Australia - Omar, Marhanis; Crowe, Andrew; Hughes, Jeffrey (International Journal of Pharmacy and Pharmaceutical Sciences, 2013)
What is known: Ethnic variation as well as the population frequency of the MDR1 C3435T transition has been observed in the few other populations but not in Australians. Objective: This study aimed to investigate the distribution of the single nucleotide polymorphism C3435T in exon 26 of the MDR1 gene among people in Western Australia, Australia. Methods: Blood samples were collected from participants from a tertiary hospital in Western Australia from October 2010 to July 2011. The MDR1 C3435T polymorphism was determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results: It was found that the frequency of the homozygous 3435TT allele among the subjects was 30.77% compared to the 21.98% that carries the homozygous 3435CC allele while almost half of our study subjects are carrying the heterozygous 3435CT allele. Our study shows similarity with C3435T genotype distribution among New Zealander and Asians population which could be attributed to the close geography between Australia and New Zealand with other part of Asia and possibly due to high migration between these countries. What is New: This study included Australian patients. Conclusion: This is the first study to illustrate the distribution of MDR1 C3435T genotypes for Australians that could be useful in predicting risk for certain disease and beneficial in tailoring a patient`s drug regimen.